2022
DOI: 10.3389/fcvm.2022.912071
|View full text |Cite
|
Sign up to set email alerts
|

Kinking of Frozen Elephant Trunk Hybrid Prostheses: Incidence, Mechanism, and Management

Abstract: IntroductionKinking of the Frozen Elephant Trunk (FET) stent graft is one of the most devastating complications of the FET procedure. It can present post-operatively with reduced arterial pressures in the lower limbs and intermittent claudication. However, it can also be visualized intra-operatively by the surgeons. Unresolved kinking of the stent graft can result in intraluminal thrombus formation and subsequent multi-organ septic emboli.AimsThe main scope of this review is to collate, summarize and present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Only a few cases have been reported in a recent review, but graft kinking is another critical complication, with multiple theories regarding its mechanism, including the direction of blood flow and the length and position of the stent-graft in relation to the aortic curvature [88]. Balloon dilatation, TEVAR, or open repair have been proposed as possible management strategies.…”
Section: Stent-graft Kinkingmentioning
confidence: 99%
“…Only a few cases have been reported in a recent review, but graft kinking is another critical complication, with multiple theories regarding its mechanism, including the direction of blood flow and the length and position of the stent-graft in relation to the aortic curvature [88]. Balloon dilatation, TEVAR, or open repair have been proposed as possible management strategies.…”
Section: Stent-graft Kinkingmentioning
confidence: 99%
“…Kinking of the FET HP is an uncommon yet life-threatening complication of FET. It is thought that sufficient retrograde blood flow, longer prosthesis and the positioning of the stent graft at the level of the aorta all contribute to its incidence ( 61 ). As a result of the turbulence of blood, this can result in fatal outcomes, such as dislodging septic emboli and end-organ ischaemia.…”
Section: Kinking and Coagulopathymentioning
confidence: 99%
“…Kreibich et al ( 5 ) reported that 2 out of 35 patients developed kinking post-FET using THP. Other devices quoted in the literature that were associated with kinking involve 3 out of 38 patients (8%) with the branched 1-piece graft from Yuhengjia Sci-Tech Co. and 1 out of 60 patients (2%) with the Frozenix graft ( 61 ).…”
Section: Kinking and Coagulopathymentioning
confidence: 99%
“…In rarer cases, reintervention can also include graft kinking and aorto-oesophageal fistulae. Interestingly, the choice of FET device as well as its size and length can help minimise the risk of reintervention ( 17 , 18 ).…”
mentioning
confidence: 99%